Flipped Publishing: A New Paradigm for Medical Textbooks (Res Medica, 2015)
Medical textbooks remain an integral component of the undergraduate education pathway. These texts are traditionally prepared by senior clinicians or academics, based on their long experience of the subject matter. Medical students and junior doctors are commonly asked to review these books, but often have little role in influencing the content. This article will discuss the opening of a new paradigm in medical publishing, whereby students and junior doctors (juniors) take the lead in planning and producing the content of their textbooks with senior clinicians taking the role of reviewer.